Impact Of Investors’ Sentiment On Share Prices: Potential Investing Strategies During The Covid-19 Outbreak - Che Yahya, Norliza (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2 (2022): Theme: Contemporary Issues in Business and Management, 2022)
The resurgence of the Covid-19 infections worldwide and the downtrend in stock markets give anxiety to investors on the potential loss of their investment capital and value. At present, investors are motivated to search for the appropriate investment strategies for better protection of their investment value. There will be opportunities amid the risks, especially for investors with a long-term horizon. Still, the opportunities are difficult to exploit without the understanding of how the share prices of companies are influenced during the Covid-19 outbreak. The sentiment of investors, although it can be challenging to estimate, is posited as one of the dominating factors to the movement of share prices. Investors' sentiment, which will be negative with a pessimistic view on the future trends of certain stocks, may cause some stocks to be severely undervalued, offering other investors an opportunity to buy the shares at discounted price. As history from the previous infectious disease outbreaks reveals that their shocks to stock market usually are temporary, a buying strategy to stocks that have been dipped but are fundamentally strong can be suitable to apply for investors with long term objectives. The proposal to any potential investing strategy, however, is not plausible to develop without the understanding of how investors' sentiment during this pandemic affect the share prices of companies. Thus, using panel data regression analysis, this study is proposed to examine the daily impact of investors' sentiment on share prices of the Malaysian listed companies from January 2020, the month when the Covid-19 case reached Malaysia, to May 2022. Relying on the internet search-based data, Google Search Index volume (SIV) to measure the investors' sentiment reaction or sentiment, this study predicts that the sentiment of investors will uniquely impact the movement in the share prices of companies from specific sectors Research paper Keywords: Investors Sentiment; Share Prices; Investment Strategies; Covid-19 Reference to this paper should be made as follows: Che Yahya, N. (2022). Impact Of Investors’ Sentiment On Share Prices: Potential Investing Strategies During The Covid-19 Outbreak. Journal of Entrepreneurship, Business and Economics , 10 (2), 18–43.